Graft-versus-host disease: teaching old drugs new tricks at less cost - Farhan, Shatha; Holtan, Shernan G. (Frontiers in Immunology, 2023)
Graft-versus-host disease (GVHD) remains a major cause of morbidity and mortality after allogeneic stem cell transplant (SCT). Currently, more patients can receive SCT. This is attributed to With the use of reduced intensity regimens allowing transplantation of older patients and those with comorbidities, and the use of different GVHD prophylaxis that breaks the barrier of human leukocyte antigen allowing an increase in the donor pool., more patients can receive SCT. Once an area with relatively few clinical trial options, there has been an increase in the interest in GVHD prophylaxis and treatment, which has led to many US Food and Drug Administration (FDA) approvals. Although there is considerable excitement over novel therapies, many patients may not have access to them due to geographical or other resource constraints. In this review article, we summarize the latest evidence on how we can continue to repurpose drugs for GVHD prophylaxis and treatment. Drugs covered by our review include those that have been FDA approved for other uses for at least 15 years (since 2008); thus, they are likely to have generic equivalents available now or in the near future.